Genome-wide identification and extensive analysis of rice-endosperm preferred genes using reference expression database - Hong, Woo-Jong; Yoo, Yo-Han; Park, Sun-A; Moon, Sunok; Kim, Sung-Ruyl; An, Gynheung; Jung, Ki-Hong (Journal of plant biology = Singmul Hakhoe chi, 2017)
Studying endosperm development in crop species enables us to understand the molecular mechanisms for producing and metabolizing carbohydrates as a main energy source. A significant accumulation of genome-wide transcriptome data can enhance the performance of metaexpression data for diverse applications. Using a gene search tool in Genevestigator (https://genevestigator.com/) for anatomical samples, we first conducted a meta-anatomical expression analysis based on 2566 Affymetrix array data in rice ( Oryza sativa ) and intended to identify 400 endospermpreferred probes. Tissue-preferred expression patterns were confirmed by performing an additional meta-analysis of anatomical expression data comprising 219 spatial or temporal Agilent 44K array data. We then identified 299 genes that showed strong endosperm-preferred expression. The functional significance of 24 previously characterized genes was evaluated, and tissue-specific expression patterns of two genes were validated using a GUS reporter system. This second approach demonstrated that new tools are available for delivering agronomic traits in the endosperm. MapMan (mapman.gabipd.org/) analysis revealed the Metabolism and Regulation overviews associated with the process of endosperm development. In particular, the starch metabolism pathway is very closely related to that process in rice. We then constructed a regulatory network using both KEGG (www. genome.jp/ kegg/) pathway information for our candidate genes and a predicted protein–protein interaction network tool. Examination of an osbzip58-1 mutant with defects in endosperm development was combined with global transcriptome data in the network. Our results indicated that osbzip58-1 regulates the starch and sucrose metabolism pathways as well as the production of seed storage protein precursors. This new fundamental information adds to our understanding about the molecular mechanism for endosperm development in rice, and the resulting data will contribute to future studies that work to enhance the agronomic trait(s) associated with the endosperm.